2023
DOI: 10.3390/bios13080810
|View full text |Cite
|
Sign up to set email alerts
|

Laser Scribing Turns Plastic Waste into a Biosensor via the Restructuration of Nanocarbon Composites for Noninvasive Dopamine Detection

Abstract: The development of affordable and compact noninvasive point-of-care (POC) dopamine biosensors for the next generation is currently a major and challenging problem. In this context, a highly sensitive, selective, and low-cost sensing probe is developed by a simple one-step laser-scribing process of plastic waste. A flexible POC device is developed as a prototype and shows a highly specific response to dopamine in the real sample (urine) as low as 100 pmol/L in a broad linear range of 10−10–10−4 mol/L. The 3D to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…Also, the light diffusion kinetics in the polymeric medium is not even in the exposed area at a low absorption wavelength with Gaussian beam distribution. While increasing the exposure time and light intensity, the optically induced photochemical evolution/coupling and photolysis effects play a signi cant role [26][27][28][29][30][31]. After careful analyses of the FT-IR/Raman spectra, HRTEM and EDS mapping results, we found that the solidi ed area formed at the range of 2 mW-15 mW is the result of further ICA conversion into an indene dimer molecule along with NR (Fig.…”
Section: Formation Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the light diffusion kinetics in the polymeric medium is not even in the exposed area at a low absorption wavelength with Gaussian beam distribution. While increasing the exposure time and light intensity, the optically induced photochemical evolution/coupling and photolysis effects play a signi cant role [26][27][28][29][30][31]. After careful analyses of the FT-IR/Raman spectra, HRTEM and EDS mapping results, we found that the solidi ed area formed at the range of 2 mW-15 mW is the result of further ICA conversion into an indene dimer molecule along with NR (Fig.…”
Section: Formation Mechanismmentioning
confidence: 99%
“…Because the resulting product is obtained by polymer burning, these ndings imply that precise control of experimental parameters are most crucial for producing heterostructure in a controlled manner. The results of our recent studies [27,28] show that the energy gradient of the Gaussian beam from the laser and the precursor material's capacity to absorb light can be used to create novel composites with high performance. Yet, from a single, well-known quantity like laser uence/power density, it is still unknown how to determine the precise conditions for a laser lithography experiment, which is controlled by numerous factors.…”
Section: Design Principalmentioning
confidence: 99%
See 1 more Smart Citation